Essential Mineral Profile of Lingula unguis from Mutiara Beach Waters as a Functional Food Candidate - Minsas , Sukal; Warsidah, Warsidah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Stunting is a national health problem that is still of great concern to the government. One effort to prevent stunting is to search for local food ingredients that contain nutritional value as an indicator of their ability to become anti-stunting candidates. Sea bean sprouts or also called Lingua unguis are a type of shellfish found on Mutiara Beach, Sukadana City, North Kayong, empirically used by coastal communities as a family food menu. This study aims to determine the content of the essential metals iron (Fe), zinc (Zn) and iodine (I) as elements of nutritious food used to prevent stunting. The research results showed that the Fe, Zn and I contents were 92.09 ppm, 26.44 ppm and 15.2 ppm respectively. Determination of essential mineral content using the Inductively Coupled Plasma (ICP) Mass Spectorophotometer (ICP-MS) instrument.